From Riba to Zakat: An Analytical Study of Islamic Economic Principles and Their Distinction from Conventional Economics - Nahid Ayad; Mowafg Abrahem Masuwd; Safa Alrumayh (Bulletin of Islamic Research, 2025)
This research explores the foundational principles and ethical framework of Islamic economics as a distinct paradigm from conventional economic systems. Anchored in Islamic legal and moral philosophy, the study examines core concepts such as the prohibition of Riba (interest), the obligation of zakat (almsgiving), the avoidance of Gharar (excessive uncertainty), and the requirement for halal (permissible) transactions. Using a qualitative content analysis approach, the research draws on instructional material to identify how these principles are articulated and positioned within Islamic economic thought. The analysis reveals that Islamic economics is not merely a financial model but a value-based system emphasizing justice, social welfare, and divine accountability. Unlike conventional economics, which prioritizes utility maximization and market efficiency, Islamic economics centers on moral responsibility, risk-sharing, and ethical profit. The findings highlight the potential of Islamic economics to address contemporary issues such as inequality and unsustainable growth. This study contributes to the literature by offering a structured interpretation of Islamic economics grounded in scriptural sources and pedagogical content. Its originality lies in clarifying the ethical-spiritual foundation of Islamic economics and its relevance in modern discourse on sustainable and equitable economic systems.